Examining service quality and social impact perceptions of the 2016 Rio de Janeiro Olympic Games. Issue 2 (8th May 2018) - Ribeiro, Tiago Miguel; Correia, Abel; Biscaia, Rui; Figueiredo, Carlos
Abstract : Purpose: The purpose of this paper is to examine the effects of service quality on perceived positive and negative social impact of the 2016 Rio de Janeiro Olympic Games. Design/methodology/approach: A field study was conducted in Rio de Janeiro, and data were collected from residents who attended the Olympic Games through a self-administered questionnaire ( n =519). The questionnaire included measures of perceived service quality, positive and negative social impact. A confirmatory factor analysis analysed the psychometric properties of the constructs, and a subsequent structural equation model examined the relationships between service quality and social impact perceptions. Findings: The results show good psychometric properties of a multidimensional construct of service quality composed of the technical, functional, aesthetic, access, accommodation and complementary events dimensions. The service quality construct was significantly related to both positive social impact (city image and community pride enhancement, social experiences and public infrastructures) and negative social impact (social conflicts and costs) perceptions. Originality/value: This study contributes to the literature by examining the role of service quality in sport mega-events and testing on different facets of social impact. The findings highlight that social atmosphere and new experiences in the Olympic Games are critical when planning these events.